Inulin as an ingredient for improvement of glycemic response and sensory acceptance of breakfast cereals - Ferreira, Suzane Martins; Capriles, Vanessa Dias; Conti-Silva, Ana Carolina [UNESP] (Elsevier, 2021)
Inulin-type fructans have been used as an ingredient to partially replace starchy flours in foods such as pasta, confectionery, breads, sauces and desserts, as they have the potential to improve technological properties, nutritional quality of the products and reduce glycemic response. Therefore, this study aimed evaluating the impact of inulin on the physical properties, proximate composition, glycemic response and sensory acceptance of corn breakfast cereals. A mixture of corn grits and inulin was extruded in a single screw extruder, at a feed rate of 247 g/min, temperatures in the shearing zones at 140 °C and screw speed of 192 rpm. The addition of inulin did not impair the physical properties of breakfast cereals, such as expansion ratio, density, instrumental force and color. Moreover, inulin did not affect the acceptance of products, as well as having a positive impact on them. Extrudates with inulin presented a high fiber level and moderate glycemic load, in contrast to the control extrudate that had low fiber level and high glycemic load. Therefore, the addition of inulin in breakfast cereals is promising and may contribute to increasing the consumption of products with aggregated nutritive value.
Keywords: Extrusion-cooking; Fructan; Glycemic index; Glycemic load; Sensory quality